Epidemiology of stroke in Pakistan and its provinces, 1990–2021: Findings from the global burden of disease study 2021 - Sufyan Shahid; Ali Dheyaa Marsool; Maha Sajjad; Muneeb Saifullah; Muhammad Awais Alam; Syed Ijlal Ahmed; Raheel Ahmed; Fahd Sultan (Global Epidemiology, 2025)
Background: Despite stroke being a leading cause of death in Pakistan, no study has comprehensively analyzed national and regional trends over time. This gap limits understanding of the evolving burden and underlying risk factors. Methods: We analyzed regional stroke trends in Pakistan from 1990 to 2021 using Global Burden of Disease (GBD) 2021 data. Age-standardized incidence, prevalence, mortality, disability-adjusted life years (DALYs), and 18 modifiable risk factors were analyzed across provinces. Joinpoint regression identified temporal trends through annual percent changes (APCs), and population attributable fractions (PAFs) quantified risk contributions. All estimates incorporated 95 % uncertainty intervals and underwent sensitivity testing to ensure robustness. Findings: In 2021, stroke was the second leading cause of death in Pakistan, responsible for 99,759 deaths, with an incidence of 153 and a prevalence of 1088 per 100,000 population. Age-standardized rates for incidence, prevalence, mortality, and DALYs declined overall from 1990 to 2021 (ASIR AAPC: −0.15 %), though reductions were modest. Regional trends showed the steepest declines in Islamabad and Punjab, while Balochistan experienced an increase in mortality (ASMR AAPC: +0.03 %) and DALYs (+0.05 %). Sex-specific trends showed greater declines in incidence and mortality among females, while DALY reductions were modest in both sexes, reflecting ongoing disability. High systolic blood pressure was the leading risk factor for stroke mortality (25.2 per 100,000) and DALYs (674.9 per 100,000), followed by household air pollution, ambient particulate matter, and high fasting glucose. These findings reflect the combined influence of cardiometabolic, environmental, and behavioral risks on Pakistan's evolving stroke burden. Interpretation: Despite modest improvements, stroke remains a major health challenge in Pakistan, with rising long-term disability and stark regional inequalities. Strengthening prevention, equitable access, and post-stroke care is essential to curb the growing burden.